2020
DOI: 10.1016/j.rssm.2019.100444
|View full text |Cite
|
Sign up to set email alerts
|

Different samples, different results? How sampling techniques affect the results of field experiments on ethnic discrimination

Abstract: Different samples, different results? How sampling techniques affect the results of field experiments on ethnic discrimination Research in Social Stratification and Mobility

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Questions remain, however, about the generalizability of findings from field experiments conducted through individual online platforms, given that these sources may be limited to a particular slice of the broader labor market. While there is evidence from the German housing market that ethnic discrimination does not vary by the source of the posting (Auspurg, Schneck, and Thiel 2020), to our knowledge similar work has not been conducted for the labor market or in the United States. Why might we expect to see variation in discrimination across job posting sources?…”
mentioning
confidence: 74%
“…Questions remain, however, about the generalizability of findings from field experiments conducted through individual online platforms, given that these sources may be limited to a particular slice of the broader labor market. While there is evidence from the German housing market that ethnic discrimination does not vary by the source of the posting (Auspurg, Schneck, and Thiel 2020), to our knowledge similar work has not been conducted for the labor market or in the United States. Why might we expect to see variation in discrimination across job posting sources?…”
mentioning
confidence: 74%
“…This variation in the prevalence of disease may reflect the different management systems, the amount of contamination of the pastures with the tapeworm eggs, and the attempts for controlling and preventing infection [ 25 , 26 ]. In addition, the methods of selecting the samples and the techniques applied to detect infection could probably have effective roles in determining prevalence [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Posts are manually scanned for duplicate address, housing development, company, and contact information. While this may bias the sample toward landlords with fewer units, previous research has shown that this is unlikely to bias the results (Auspurg et al, 2020).…”
Section: Samplingmentioning
confidence: 97%